Adverse events of recreational cannabis use reported to the French addictovigilance network (2012–2017). Issue 10 (19th April 2021) - Bouquet, Emilie; Pain, Stéphanie; Eiden, Céline; Jouanjus, Emilie; Richard, Nathalie; Fauconneau, Bernard; Pérault‐Pochat, Marie‐Christine; ,
Abstract : Aims: To describe the adverse events (AEs) of recreational cannabis use in France between 2012 and 2017. Methods: AEs related to recreational cannabis use, alone or in combination with alcohol and/or tobacco reported to the French Addictovigilance Network were analysed (excluding cannabidiol and synthetic cannabinoids). Results: Reporting of AEs tripled between 2012 ( n = 179, 6.3%, 95% confidence interval [CI] = 5.4–7.2) and 2017 ( n = 562, 10.1%, 95% CI = 9.3–10.9), reaching 2217 cases. They concerned mainly men (76.4%) and users aged between 18 and 34 years (18–25: 30.9%; 26–34: 26.3%, range: 12–84 years). Cannabis was mainly inhaled (71.6%) and exposure was most often chronic (64.2%). Many types of AEs were reported: psychiatric (51.2%), neurological (15.6%), cardiac (7.8%) and gastrointestinal (7.7%), including unexpected AEs ( n = 34, 1.1%). The most common effect was dependence, ranging from 10.1% (95% CI = 7.9–12.3) to 20.3% (95% CI = 17.3–23.2) over the study period. Cannabinoid hyperemesis syndrome ( n = 87, 2.8%) emerged from 2015. Deaths accounted for 0.2% of all AEs (4 men and 3 women aged on average 35 years). A chronic pattern of cannabis use was reported in 4 of them (intracranial hypertension in the context of lung cancer, suicide, cerebral haematoma, neonatal death with concomitant chronic alcohol use), while in the other cases the toxicological analysis identified cannabis use (ruptured aneurysm and unknown aetiology). Conclusion: This study showed a multitude of AEs related to recreational cannabis use, including unexpected AEs and deaths. It highlights the problem of dependence and the emergence of cannabinoid hyperemesis syndrome.